Internet connectivity disruption in Venezuela (Venezuela) - Voidly (2026)
CRITICAL severity mixed detected in Venezuela. Confidence: 75%. Data sourced from IODA, CensoredPlanet.
Censorship Incident ID: VE-2026-0160
Keywords: censorship; VE; mixed; critical